Educational psychology and educational practices mediated by ICT: State of the art (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on publications in high impact journals indexed inthe Scopus database related to Psychology in Education and Educational Practices mediatedby ICT during the period 2010-2020. As a result of the first search, a total of 715documents were classified according to their year of publication, country of origin, area ofknowledge, authors and type of publication. In this way, the essential characteristics of thepublications on the above-mentioned topic were identified. Similarly, the position ofdifferent authors was analyzed from a qualitative perspective through their research oneducational practices mediated by ICT and psychology in education. The main findings ofthis paper are: The United States is the country with the highest number of publicationsregistering a total of 260 research papers published during the period between the years2010 and 2020, of which, the year with the highest number of records was 2020 with 130publications. Of the total number of identified documents, 225 are made under theories thatframe the social sciences and the most frequent type of publication for the authors was thejournal paper, 75% of the total scientific production being published by this means. Thanksto the above, the final document is constructed through conclusions that could constitutesupport material for future research related to the topic proposed in this document.